2001
DOI: 10.1007/bf02373580
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of a number of alternative negative electrode materials for use in lithium cells

Abstract: Abstract. There is a considerable interest in the replacement of graphite as the negative electrode reactant in rechargeable lithium batteries by composite electrodes containing alloys or convertible oxides. Some such materials can have much higher theoretical specific capacities than graphite, more than a factor of ten in some cases. In addition it would be desirable to eliminate the irreversible loss of capacity during the first charging cycle that is characterisitic of graphite electrodes, as well to raise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 12 publications
2
30
0
Order By: Relevance
“…The electrochemical behavior of different silicides, among others FeSi 2 , CoSi 2 , TiSi 2 , and NiSi 2 , was investigated in 2001 by Netz et al in Li metal cells and they reported that TiSi 2 does not react with Li, whereas FeSi 2 and CoSi 2 show very low capacities below 60 mAh · g –1 , whereas the capacity of NiSi 2 is higher with 200 mAh · g –1 . In contrast to that, Fleischauer et al reported that CoSi 2 is inactive towards lithiation when investigating TM‐Si thin films …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrochemical behavior of different silicides, among others FeSi 2 , CoSi 2 , TiSi 2 , and NiSi 2 , was investigated in 2001 by Netz et al in Li metal cells and they reported that TiSi 2 does not react with Li, whereas FeSi 2 and CoSi 2 show very low capacities below 60 mAh · g –1 , whereas the capacity of NiSi 2 is higher with 200 mAh · g –1 . In contrast to that, Fleischauer et al reported that CoSi 2 is inactive towards lithiation when investigating TM‐Si thin films …”
Section: Resultsmentioning
confidence: 99%
“…While most of the transition metal (TM) silicides, like FeSi 2 , CoSi 2 , TiSi 2 , or NiSi 2 have been reported to have no or only a minor reversible capacity at room temperature and are considered as “inactive”, other metal silicides e.g. Mg 2 Si react reversibly with Li and are, thus, considered “active” …”
Section: Introductionmentioning
confidence: 99%
“…Lithiation and delithiation properties of silicides have not yet been investigated in ionic liquid electrolytes. On the other hand, in organic electrolytes, some groups have reported the charge‐discharge properties of some silicides . However, the groups have performed insufficient characterization: they characterized prepared samples by only X‐ray diffraction (XRD), which detects the crystalline material but cannot detect amorphous ones.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in organic electrolytes, some groups have reported the charge-discharge properties of some silicides. [23][24][25][26] However, the groups have performed insufficient characterization: they characterized prepared samples by only X-ray diffraction (XRD), which detects the crystalline material but cannot detect amorphous ones. Assuming that the synthesized samples include amorphous Si (a-Si), an estimated reversible capacity should largely differ.…”
Section: Introductionmentioning
confidence: 99%
“…A forming alloy of Si and transition metal elements is one of some approaches to solve the problem. Many researchers have synthesized various anodes based on transition metal silicides, Mg2Si [4], CaSi2 [5,6], TiSi2 [7], VSi2 [8], CrSi2 [9], FeSi2 [8,10,11], CoSi2 [5,12], NiSi2 [5,8,13], and MoSi2 [9]. Since Mg and Ca are Li-active elements, Mg2Si and CaSi2 showed relatively high capacities at the first cycles.…”
Section: Introductionmentioning
confidence: 99%